AB0499 Post-discontinuation treatment patterns for tumor necrosis factor-blockers in rheumatoid arthritis patients in the US. (23rd January 2014) - Schabert, V.F.; Fox, K.M.; Watson, C.; Yeaw, J.; Goodman, S.; Gandra, S.R.
Abstract : Background: Etanercept (ETN), adalimumab (ADA), and infliximab (INF) are the 3 most frequently prescribed tumor necrosis factor (TNF)-blocker therapies that are approved by the US Food & Drug Administration for treatment of moderate to severe rheumatoid arthritis (RA). Clinical guidelines and published studies do not offer clear recommendations for treatment options after discontinuing a TNF-blocker for RA. Treatment patterns after TNF-blocker discontinuation have not been well characterized. Objectives: To estimate the proportion, among RA patients enrolled in US managed care plans, who discontinued their index (initial) TNF-blocker treatment (ETN, ADA, or INF), who subsequently restarted their index TNF-blocker or switched to another biologic or nonbiologic therapy. Methods: The IMS LifeLink™ Health Plan Claims database was used to identify RA patients who received ETN, ADA, or INF between 1 January 2005 and 31 March 2009. Patients with psoriasis, psoriatic arthritis, ankylosing spondylitis, Crohn's disease, ulcerative colitis, or juvenile idiopathic arthritis during the 180 days prior to index TNF-blocker therapy were excluded. Patients were considered discontinued from index TNF-blocker therapy upon switch to a non-index TNF-blocker therapy for RA or >45-day gap in index TNF-blocker therapy. The index date was the date of switch or the first day of 45-day gap, whichever came first. Patients had to be continuously enrolled in the health plan and were followed for 360 days after index date; study end date was 31 March 2010. Patients were categorized into mutually exclusive groups, in descending order, based on whether they: 1) restarted their index TNF-blocker, 2) switched to another TNF-blocker (ETN, ADA, or INF), 3) switched to other biologics, 4) switched to a non-biologic therapy, or 5) had no new treatment. Results: Among an initial 18094 RA patients who were on TNF-blocker therapy, 9952 RA patients (5155 ETN; 2513 ADA; 2284 INF) discontinued treatment, met selection criteria, and were included in this analysis. Mean age at discontinuation was 49.5 yrs; 76.6% were women. Within 360 days of discontinuing a TNF-blocker, 52.2% of patients restarted their index TNF-blocker (59.5% of ETN; 45.2% of ADA; 43.1% of INF; p<0.001 for ADA and INF vs ETN; 61-66% restarted within the first 3 months); 16.5% switched to another TNF-blocker (16.5% from ETN; 19.2% from ADA; 13.8% from INF); 5.7% switched to other biologics (2.7% from ETN; 5.4% from ADA; 12.7% from INF); 5.4% switched to a non-biologic therapy (4.7% from ETN; 6.0% from ADA; 6.5% from INF); and 20.2% had no new treatment (16.6% from ETN; 24.2% from ADA; 23.8% from INF). Conclusions: TNF-blocker restarts occurred frequently after discontinuation of index TNF-blocker therapy, suggesting that long gaps (>45 days) in TNF-blocker therapy may be common practice among RA patients. A significantly higher proportion of ETN patients restarted their index TNF-blocker within 1 year of discontinuation compared with ADA and INF patients. After discontinuation of index TNF-blocker therapy, 19% of ETN patients, 25% of ADA patients, and 27% of INF patients switched to another TNF-blocker or other biologic therapy. This study sponsored by Immunex, a wholly owned subsidiary of Amgen Inc. and by Wyeth, which was acquired by Pfizer Inc. Disclosure of Interest: V. Schabert Consultant for: Amgen Inc., K. Fox Consultant for: Amgen Inc., C. Watson Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Yeaw Consultant for: Amgen Inc., S. Goodman Consultant for: Amgen Inc., S. Gandra Shareholder of: Amgen Inc., Employee of: Amgen Inc.